2017
DOI: 10.1016/j.agwat.2017.03.030
|View full text |Cite
|
Sign up to set email alerts
|

Assessing a crop water stress index derived from aerial thermal imaging and infrared thermometry in super-high density olive orchards

Abstract: 13Characterization of the spatio-temporal variability of tree water status is a prerequisite 14 to conducting precise irrigation management in fruit tree orchards. This study assessed

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
91
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 146 publications
(104 citation statements)
references
References 38 publications
12
91
1
Order By: Relevance
“…Examples are given by Gonzalez-Dugo et al [21] for almond, apricot, peach, lemon and orange orchards, by Bellvert et al [64] for a vineyard, by Gonzalez-Dugo et al [22] for pistachio and by Egea et al [65] for olive. Gago et al [60] reviewed the use of different remote sensors providing a variety of indices (NDVI, TCARI/OSAVI and PRInorm), mounted on different types of UAVs, for sustainable agriculture.…”
Section: Airborne Imagerymentioning
confidence: 99%
See 3 more Smart Citations
“…Examples are given by Gonzalez-Dugo et al [21] for almond, apricot, peach, lemon and orange orchards, by Bellvert et al [64] for a vineyard, by Gonzalez-Dugo et al [22] for pistachio and by Egea et al [65] for olive. Gago et al [60] reviewed the use of different remote sensors providing a variety of indices (NDVI, TCARI/OSAVI and PRInorm), mounted on different types of UAVs, for sustainable agriculture.…”
Section: Airborne Imagerymentioning
confidence: 99%
“…Most authors using thermal images taken from UAVs and planes reported robust relationships between the derived CWSI and main physiological variables related to water stress, such as stomatal conductance and stem or leaf water potential [56,64,65], and claimed that the approach was suitable for characterizing plant water status variability in woody crops. Remote sensing data acquired by satellite sensors can be used to derive daily evapotranspiration (ET) maps.…”
Section: Airborne Imagerymentioning
confidence: 99%
See 2 more Smart Citations
“…Among these, 700 reported studies on olive cultivation. With the constant expansion in cultivation area, cultivation technology under different site conditions has become a study focus, and high density and super-high density planting has gradually developed into a high profile field in studies of table olives and olives for oil extraction due to the significant yield improvements and other benefits, although they frequently have a negative impact on the environment [31,32,33,34]. In total, 164 papers reported studies on harvesting, and recent high-profile topics include mechanized harvesting technology and efficiency, and damage identification and reduction, especially the application of UAV photography technology in harvesting and the management of olive plantations [35,36,37,38,39].…”
Section: Contentmentioning
confidence: 99%